An Analysis of Humor Delivery Types and Functions in Family Feud Funny Moment - Devi Melisa Saragi (Prodi Sastra Inggris UKI, 2023)
Humor has played an important role in daily communication and interaction in different context and culture. The purposes of this research are : 1) to find out the types of humor delivery found in Family Feud Funny Moment; 2) to describe the function of humor delivery found in Family Feud Funny Moment. This research used qualitative descriptive method. As many as 64 data of humor were collected by observing and note taking method. All data which were obtained were analyzed by using the humor theories in order to get the types of humor delivery and the function of Humor by Attardo (1994) to get the function. The results show that the types of humor delivery implemented three different humor delivery theories, namely release, incongruiy and superiority. Of the three theories implemented, incongruity became the most dominat theory used in delivering humors which were found in 33 parts of deliveries or 51,56%. . The second result showed that there were four different functions of humor delivery found in Family Feud Funny Moment, such as defunctionalization, mediation, social management, and decommitment function. The most frequent function appeared in this event was as follow the as defunctionalization as many as 22 data (34,37%).